KEKERASAN SUAMI TERHADAP ISTRI DALAM PENDIDIKAN ISLAM (STUDI AL-QURAN SURAH AN-NISA AYAT 34-35) - Silfia Nurul Huda; Wahyu Hidayat; Wasehudin (Almarhalah: Jurnal Pendidikan Islam, 2023)
KDRT sometimes it violates the sacred bond of marriage that is polluted, this phenomenon occurs and is widely discussed, it is even necessary to return to the actual source to find a solution, so it is important to carry out a study by examining domestic violence in the perspective of the Koran, namely the study of the Koran Surah An-Nisa verses 34-35 . This study uses a qualitative approach, in which the researcher uses different types of research libraries to study different aspects of the topics discussed. This is done by looking for references related to domestic violence from journal articles, books, printed and electronic forms of law, and from the perspective of the Qur'an, verses 34-35. The study found that husbands who physically abuse the household can only do so in emergencies or in situations where they feel the need to protect their wife or children. On the other hand, forgiving your husband is better. There are several provisions outlined by the scholars and must be considered by husbands. For example, a husband may not hit his wife with a sharp, dangerous object, may not hit her face or other places that can cause harm, and may hit her if it is not harmful. Scholars agree that a husband who does not discipline his wife physically and forgives her even when she is in the wrong is the best course of action, which is similar to what the Qur'an teaches. In discussing the wife that Nusyuz only recommends how to gently advise and separate the bed/beds, the professor explains how to be gentler with his wife and avoid potential problems. Spanking is only tolerated when used in a way that doesn't hurt or upset the person being hit.